Green approaches to biocomposite materials science and engineering - Verma, Deepak, 1983-; Jain, Siddharth, 1984-; Zhang, Xiaolei, 1986-; Gope, Prakash Chandra (Hershey, PA : Engineering Science Reference, an imprint of IGI Global, 2016)
'This book explores timely research on the various available types of natural fibers and the use of these fibers as a sustainable alternative to synthetic fibers and polymers by emphasizing research-based solutions for sustainability across various industries'--
Includes bibliographical references and index.
Keywords: Fibrous composites; Sustainable engineering